An Ethnobotanical Study of Medicinal Plants in Kinmen - Huang, Shyh-Shyun; Huang, Chia-Hung; Ko, Chien-Yu; Chen, Ting-Yang; Cheng, Yung-Chi; Chao, Jung (Frontiers in Pharmacology, 2022)
Kinmen is an outlying island that has the richest plant resources in Taiwan. The objective of this study was to record the methods that people in Kinmen use medicinal plants and to analyze the cultural characteristics of their use. Field investigations were carried out in various towns and villages in Kinmen, and 80 respondents were included in the survey. The search for respondents was conducted through local elderly people and medicinal plant groups. Semi-structured interviews were conducted with the local people to obtain their knowledge of medicinal plants and how they disseminate this information. Informed consent was obtained prior to the interviews, and the following was determined: plant use value, frequency of citation, and factor of informant consensus. These parameters were used to quantify the data and measure the agreement among the respondents on using plants to treat different diseases. Finally, the survey results were compared with the representative ethnobotanical literature in neighboring areas to evaluate the similarity between plant usage in Kinmen and neighboring areas and to determine whether there are new species or novel usages in the study area. In the Kinmen area, phytotherapy is generally used by elderly people with low educational attainments. According to the survey results, 83 medicinal plants belonging to 48 families were collected. These medicinal plants were mainly distributed in the Compositae, Lamiaceae, and Solanaceae. Eighteen novel uses that have not been previously documented were found, four of which were related to newly recorded medicinal plant species in the Kinmen area. 93.98% and 65.06% of the species collected in the present study were recorded in literature from Taiwan and Fujian, respectively. This study showed that Kinmen’s ethnobotanical knowledge is closely related to the Catalogue of Medicinal Plant Resources in Taiwan, and local people indeed shared similar uses of medicinal species with people in Taiwan and Fujian (46.99%). The results from this study highlighted the importance of traditional medicine in the Kinmen area, where people have a specific understanding of using medicinal plants and communication with people in Taiwan and Fujian, China. It was found that Kinmen shares ethnobotanical knowledge with Taiwan and Fujian.